Chlamydia trachomatis screening in preterm labor: A systematic review and meta-analysis. (September 2019) - Kanninen, Tomi T.; Quist-Nelson, Johanna; Sisti, Giovanni; Berghella, Vincenzo
Abstract: Objective: Spontaneous preterm labor (PTL) is responsible for approximately half of all preterm births with intrauterine infection being an important risk factor for PTL. Chlamydia trachomatis infections have been associated with preterm prelabor rupture of membranes (P-PROM) and preterm birth, but its impact on PTL has not previously been specified. The aim of this study was to evaluate the overall prevalence of Chlamydia trachomatis infections in pregnant women with threatened PTL compared to those not in threatened PTL. Study design: A literature search was performed in electronic databases using combinations of: " Chlamydia ", "vaginal cervical infection" and "preterm labor." Cohort and case-controlled studies examining threatened PTL and Chlamydia trachomatis infection demonstrated by culture or NAAT methods at time of diagnosis of threatened labor. The Meta-analyses of Observational Studies in Epidemiology (MOOSE) guidelines for reporting of observational studies for systematic reviews was used. Bias was assessed with the Methodological Index for Non-Randomized Studies (MINORS) score. Meta-analysis was performed using a random effects model. Results: Four studies were identified. A total of 591 women were included, 309 in the threatened PTL, and 282 controls not in threatened PTL. Women presenting in PTL had an increased risk of screening positive for Chlamydia trachomatis compared to the control group (27/308 (9%) vs 3/282 (1%); OR 7.74, 95% CI 2.64–22.71). Conclusions: The incidence of Chlamydia trachomatis in women with threatened PTL is approximately 9%, and significantly increased compared to asymptomatic controls. Women with threatened PTL should be considered for screening for Chlamydia trachomatis.